Sputum IL-5 concentration is associated with a sputum eosinophilia and attenuated by corticosteroid therapy in COPD. - Bafadhel, M; Saha, S; Siva, R; McCormick, M; Monteiro, W; Rugman, P; Dodson, P; Pavord, I; Newbold, P; Brightling, C (2009)
BACKGROUND: Airway inflammation in chronic obstructive pulmonary disease (COPD) is predominately neutrophilic, but some subjects demonstrate eosinophilic airway inflammation. Whether these inflammatory phenotypes have differential cytokine and chemokine expression is unknown. OBJECTIVES: To assess the sputum concentrations of cytokines and chemokines and their response to oral corticosteroid therapy in COPD subjects with or without a sputum eosinophilia. METHODS: Cytokine and chemokine concentrations were measured using the meso-scale device platform. To assess validity, recovery of exogenous spikes was examined. The concentrations of the validated mediators were measured in COPD sputum from subjects with or without a sputum eosinophilia. In a subgroup with a sputum eosinophilia, the response to oral prednisolone 10 mg for 1 month was examined. RESULTS: The recovery in sputum of exogenous spiked mediators was >80% in 11/26 cytokines and chemokines. In supernatants from eosinophilic (n = 39) versus non-eosinophilic (n = 59) sputa, the geometric mean (95% CI) concentration was increased for IL-5 [9.0 (4.5-18) pg/ml vs. 3.6 (2.7-6.3) pg/ml, p = 0.03]. IL-5 alone was correlated with sputum eosinophil counts (r = 0.33, p = 0.001), and was attenuated following treatment with prednisolone [n = 9; mean difference 2.3 pg/ml (0.2-4.3), p = 0.032]. CONCLUSION: We have validated the use of the meso-scale device platform for cytokine and chemokine measurements in the sputum supernatants in COPD. Sputum IL-5 was associated with a sputum eosinophilia and was attenuated following oral corticosteroid therapy. Whether this cytokine is important in the pathogenesis of COPD in a subgroup of patients warrants further investigation.